Late Manifestation of Subclinical Hyperthyroidism After Goitrogenesis in an Index Patient with a N670S TSH Receptor Germline Mutation Masquerading as TSH Receptor Antibody Negative Graves’ Disease - Schaarschmidt, J.; Paschke, S.; Özerden, M.; Jäschke, H.; Huth, S.; Eszlinger, M.; Meller, J.; Paschke, R. (Hormone and Metabolic Research, 2012)
In 27 families with familial non-autoimmune hyperthyroidism (FNAH) reported up to date, the onset of hyperthyroidism varies from 18 months to 60 years. Also the manifestation of goitres is variable in these families. A 74-year-old woman first presented at the age of 69 years with tachyarrhythmia and hypertension. After initial treatment of her hypertension and oral anticoagulation for her intermittent atrial fibrillation, a thyroid workup revealed a suppressed TSH and normal fT3 and fT4. TPO, TSH receptor (TSHR), and thyroglobulin antibodies were negative. Thyroid ultrasound revealed a thyroid volume of 102 ml with several nodules with diameters of up to 2.6 cm right and up to 1.8 cm left. Scintigraphy showed a homogeneous Technetium-99 m (99 mTc) uptake of 1.27%. She was subsequently treated with 1 GBq radioiodine (131I). At the age of 74, her thyroid function was normal and her thyroid volume decreased to 90 ml. Because of the diffuse 99 mTc uptake and the negative TPO, TSHR, and thyroglobulin antibodies, genetic analysis of her TSHR gene was performed, in spite of her negative family history for hyperthyroidism. Sequencing revealed a N670S TSHR germline mutation. Previous in vitro characterisation of this TSHR mutation suggests a weak constitutive activity, yet the experimental data are ambiguous. This case illustrates the necessity to analyse patients with hyperthyroidism accompanied by diffuse 99 mTc uptake and negative TPO, TSHR, and thyroglobulin antibodies for TSHR germline mutations. Moreover, it demonstrates that TSHR germline mutations may first lead to longstanding nodular goitrogenesis before the late manifestation of subclinical hyperthyroidism.
Keywords: hyperthyroidism; thyroid-stimulating hormone; Graves’ disease; thyroid function; TSHR mutation